Studi Morfometrik Hornstedtia leonurus (J.Koenig) Retz. (Zingiberaceae) dan Kerabat Dekatnya dalam Tribe Alpiniae di Sumatera Barat - Titi Lestari; Nurainas Nurainas; Syamsuardi Syamsuardi (Universitas Andalas, 2015)
Hornstedtia leonurus is one species of the Hornstedtia’s genera in Alpiniae Tribe (Zingiberaceae). It has unambiguous expressed some aberrations of morphological characters in what Hornstedtia should have. On the contrary, it has with it self some characters from other genera within the tribe of Alpiniae, such as Etlingera and Amomum. The research aimed to find some distorsion on morphological characters of the H. leonurus with its close selected sisters in Alpiniae Tribe (Etlingera megalocheilos and Amomum cardamomum) and determined their were characters relationship by a morphometric study. The materials collected from West Sumatra province (50 Kota, Padang and Sijunjung regency) on September until December 2015. Morphometric analysis used PAST version 2.17c and SPSS computer programs. Morphologically, H. leonurus closely related with E. megalocheilos rather than its sister in Hornstedtia genera (H. schypifera) and A. cardamomum.Keywords: Alpiniae, H. leonurus, morphometric, relationship, Zingiberaceae.